2022
DOI: 10.1007/s11403-021-00344-3
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous viral mutations, evolutionary selection, and containment policy design

Abstract: How will the novel coronavirus evolve? I study a simple epidemiological model, in which mutations may change the properties of the virus and its associated disease stochastically and antigenic drifts allow new variants to partially evade immunity. I show analytically that variants with higher infectiousness, longer disease duration, and shorter latent period prove to be fitter. “Smart” containment policies targeting symptomatic individuals may redirect the evolution of the virus, as they give an edge to varian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…AI based detector helps to reduce the mistaken alarm [58]. Other methods that are integrated with the compartmental modelling approach in the COVID-19 literature can be listed as follows: agent-based modelling [74], big data analytics [75], fuzzy set algorithm [76], Markov process [77], and system dynamics approaches [78]. Decision support systems were also developed for clinical decisions, allocation of resources, lock-down management, and optimization of response strategies [79].…”
Section: Different Methods Used In Reviewed Articlesmentioning
confidence: 99%
“…AI based detector helps to reduce the mistaken alarm [58]. Other methods that are integrated with the compartmental modelling approach in the COVID-19 literature can be listed as follows: agent-based modelling [74], big data analytics [75], fuzzy set algorithm [76], Markov process [77], and system dynamics approaches [78]. Decision support systems were also developed for clinical decisions, allocation of resources, lock-down management, and optimization of response strategies [79].…”
Section: Different Methods Used In Reviewed Articlesmentioning
confidence: 99%
“…Further, the potential impact of within-host evolution has been largely ignored, though SARS-CoV-2 has shown significant withinhost diversity (Tonkin-Hill et al, 2021;Lythgoe et al, 2021). Zhang et al (2022) demonstrated an abstract model of intra-and inter-host evolution in relation to SARS-CoV-2, but individual behaviours were not simulated; Mellacher (2022) presents a more detailed evolutionary model, but again individual behavioural responses are not represented.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Mellacher ( 2022 ) uses a detailed epidemiological agent-based model to study the emergence and diffusion of mutations. The macroeconomic impact of these, however, is not explored.…”
mentioning
confidence: 99%
“… 11 We model the emergence of a variant as an exogenous shock to the epidemiological scenario with vaccination. In more sophisticated epidemiological agent-based models such as Mellacher ( 2022 ), the emergence of variants is endogenous. While the endogenous emergence of variants is undoubtedly an appealing feature of a macro-epidemiological model, the exogeneity assumption is justified in our context because of the focus on a single region, Lombardy, within the context of a worldwide pandemic (indeed, all relevant variants of the SARS-COV2 virus discovered to date are held to have originated outside of Lombardy).…”
mentioning
confidence: 99%